HYBRID SUBJECT NEGOTIATION OVER CONFLICTING EASTERN AND WESTERN CULTURAL VALUES IN THE FAREWELL (2019) - Silvia Valentina Putri; Hujuala Rika Ayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Colonialism has created a binary identity division between